Seasonal Incidence of Flea Beetle, Chaetochnema indica Klse. on Sorghum - Patel, D. R.; Purohit, M. S. (International Journal of Economic Plants, 2015)
Studies on population dynamics of flea beetle, Chaetochnema indica Klse.infesting sorghum was made during rabi 2006-07,2007-08 and kharif 2007-08, 2008-09season at Agricultural Research Station, N.A.U., Tanchha, Dist. Bharuch. In rabi incidence of flea beetles began from second week of November and continued up to first week of February with a peak activity in first week of January, while in kharif flea beetles appeared from second week of August and remained till harvesting of crop. The peak activity found during first week of November. Flea beetle population positively influenced by maximum temperature, wind velocity and sunshine hours, whereas it was negatively influenced by minimum temperature, morning relative humidity, evening relative humidity, average relative humidity and rainy days.